Patirūp sangkhom kǣ khwāmyākčhon lot khwāmlūamlam sāng sangkhom khemkhǣng : khō̜sanœ̄ čhāk wēthī phākhī phatthanā Prathēt Thai (Thailand Development Forum : TD Forum) - ʻĀrī Hēmathulin (Khrōngkān Wēthī Phākhī Phatthanā Prathēt Thai, Sathāban Chumchon Thō̜ngthin Phatthanā, 2014)
Social reformations in Thailand.